Acute necrotizing gastritis with gangrenous stomach - Prajapati, Devendra K.; Rampal, Kapil; Prajapati, Jyoti M. (International Surgery Journal, 2017)
Acute necrotizing gastritis with gangrene of the stomach wall is a rarely encountered condition. This often a fatal condition if is attributed to vascular occlusion, chemical and mechanical injuries or infectious etiologies. We review the available literature with a case of acute necrotising gastritis with unknown etiology. Case was managed successfully with emergency partial gastrectomy.